Peningkatan Berpikir Kritis melalui Salin Tempel pada Majalah Dinding Kreatif Siswa SDN Gebang 3 Surakarta - Ani Rakhmawati; Muhammad Syafiiq Kurniawan; Rindang Anggun Istiqomah (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The making of wall magazines aims to understand how effective wall magazines (wall magazines) are in increasing the literacy of elementary school students. Wall magazine as one of the media raises students' motivation in literacy and creativity. The role of the teacher and students is needed in increasing interest in reading and creativity. Making wall magazines with student creations and displaying them makes students like to read or make a work of poetry or rhymes that are posted on the bulletin. The research results of wall magazines (mading) have a very important role both in the formation of students at SDN Gebang 3 Surakarta. Several aspects that can be formed are aspects of knowledge, aspects of skills, talents and interests. Wall magazine is one of the communication media that is posted on the wall because it contains important information about the school. The main functions of magazines are informative, communicative, recreational and creative